The S content of silicate melts at sulfide saturation: New experiments and a model incorporating the effects of sulfide composition - Smythe, D; Wood, B; Kiseeva, E (Mineralogical Society of America, 2017)
The extent to which sulfur dissolves in silicate melts saturated in an immiscible sulfide phase is a fundamental question in igneous petrology and plays a primary role in the generation of magmatic ore deposits, volcanic degassing and planetary differentiation. In igneous systems sulfide melts can be described as FeS-NiS-CuS0.5 solutions with Fe/(Fe+Ni+Cu) significantly less than 1. Despite the presence of Ni and Cu in the sulfide, however most experimental studies to date have concentrated on the effects of silicate melt composition on sulfur solubility and have used essentially pure FeS as the sulfide liquid. We have carried out 49 new experiments at pressures of 1.5-24 GPa and temperatures of 1400 to 2160°C in order to investigate the effects of sulfide composition on sulfur solubility as well as extending the pressure and temperature ranges of the available data on sulfide saturation. We find that, in the 26 compositional range of most igneous sulfide melts (Fe/(Fe+Ni+Cu) >0.6) sulfur solubility decreases linearly with Fe content such that at Fe/(Fe+Ni+Cu) of 0.6, the sulfur content at saturation is 0.6 times the value at pure FeS saturation. At lower values of Fe/(Fe+Ni+Cu) deviations from this ideal solution relationship need to be taken into consideration, however. We have treated these nonidealities by assuming that FeS-NiS-CuS0.5 liquids approximate ternary regular solutions. We have fitted our data, together with data from the literature (392 in total) to equations incorporating the effects of silicate melt composition, sulfide liquid composition and pressure on the solubility of sulfur at sulfide saturation [S]SCSS. The temperature dependence of [S]SCSS was assumed either to be an unknown or was taken 38 from 1 bar thermodynamic data. The most important best-fit silicate melt compositional term reflects the strongly positive dependence of [S]SCSS on the FeO content of the silicate melt. The best-fit value of this parameter is essentially independent of our assumptions about temperature dependence of [S]SCSS or the solution properties of the sulfide. All natural compositions considered here exhibit positive dependences of [S]SCSS on temperature and negative dependences on pressure, in accord with previous studies using smaller datasets.